How I approach: the transplant recipient with fever and pulmonary infiltrates - Kumar, Madan; Hanisch, Benjamin R. (Frontiers in Pediatrics, 2024)
Introduction: Recipients of hematopoietic stem cell transplants (HSCT) and solid organ transplants (SOT) frequently develop pulmonary infiltrates from both infectious and noninfectious etiologies. Differentiation and further characterization of microbiologic etiologies -viral, bacterial, fungal can be exceedingly challenging. Pediatric patients face unique challenges as confirmatory evaluations with bronchoscopy or lung biopsy may be limited. A generalizable approach to diagnosis and management of these conditions has not been well established. This paper will look to summarize our initial clinical approach while discussing the relative evidence informing our practices. To facilitate the discussion a pediatric case with characteristic infiltrates who has undergone HSCT is presented. Generalizable approaches to similar patients are highlighted as appropriate while highlighting considerations based on clinical course and key risk factors.